Objective Evaluation of Masticatory Function in Temporomandibular Disorders Patients - Mizuuchi, Kazue; Kobayashi, Yoshinori; Shiga, Hiroshi (Nihon Hotetsu Shika Gakkai Zasshi, 2006)
Purpose: The purpose of this experiment was to objectively evaluate the masticatory function in TMD (Temporomandivular disorders) patients. Methods: The quantitative indicators of muscular activity, stability of movement, and masticatory efficiency during mastication were compared among the following three groups; 10 healthy subjects, 10 patients with arthrogenous TMD, and 10 patients with myogenous TMD. For muscular activity, the integral value of the masseter muscular activity was calculated. For stability of movement, a comprehensive indicator was established after principal component analysis using the data of the seven indicators of stability of path and rhythm. For masticatory efficiency, the amount of glucose extraction after gummy-jelly chewing was measured by a blood glucose testing device. Results: The cumulative value of masseter muscular activity and the amount of glucose extraction after gummy-jelly chewing were larger in the healthy subject group than in the groups with arthrogenous or myogenous TMD, and these differences between the healthy subject group and the other two groups were statistically significant. On the other hand, the value of the comprehensive indicator was significantly smaller in the healthy subject group than in the groups with arthrogenous or myogenous TMD. Conclusion: It was suggested that the masticatory function in TMD patients is much inferior to that in healthy subjects.